Deficiency of MicroRNA-23-27-24 Clusters Exhibits the Impairment of Myelination in the Central Nervous System. (22nd March 2023) - Tsuchikawa, Yuji; Kamei, Naosuke; Sanada, Yohei; Nakamae, Toshio; Harada, Takahiro; Imaizumi, Kazunori; Akimoto, Takayuki; Miyaki, Shigeru; Adachi, Nobuo
Abstract : Several microRNAs (miRNAs), including miR-23 and miR-27a have been reportedly involved in regulating myelination in the central nervous system. Although miR-23 and miR-27a form clusters in vivo and the clustered miRNAs are known to perform complementary functions, the role of these miRNA clusters in myelination has not been studied. To investigate the role of miR-23-27-24 clusters in myelination, we generated miR-23-27-24 cluster knockout mice and evaluated myelination in the brain and spinal cord. Our results showed that 10-week-old knockout mice had reduced motor function in the hanging wire test compared to the wild-type mice. At 4 weeks, 10 weeks, and 12 months of age, knockout mice showed reduced myelination compared to wild-type mice. The expression levels of myelin basic protein and myelin proteolipid protein were also significantly lower in the knockout mice compared to the wild-type mice. Although differentiation of oligodendrocyte progenitor cells to oligodendrocytes was not inhibited in the knockout mice, the percentage of oligodendrocytes expressing myelin basic protein was significantly lower in 4-week-old knockout mice than that in wild-type mice. Proteome analysis and western blotting showed increased expression of leucine-zipper-like transcription regulator 1 (LZTR1) and decreased expression of R-RAS and phosphorylated extracellular signal-regulated kinase 1/2 (pERK1/2) in the knockout mice. In summary, loss of miR-23-27-24 clusters reduces myelination and compromises motor functions in mice. Further, LZTR1, which regulates R-RAS upstream of the ERK1/2 pathway, a signal that promotes myelination, has been identified as a novel target of the miR-23-27-24 cluster in this study.